Reinvestigating millennial shopping behavior on the sharing economy platform: The moderating role of COVID-19 awareness level - Ashoer, Muhammad; Karim, Kasnaeny; Syahnur, Muhammad Haerdiansyah; Ating, Rashid (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
Drawing from the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), this study aims to develop a predictive model concerning the shopping behaviour of millennials within the realm of the sharing economy (SE) mobile application. To accommodate prior research findings while providing novelty, this study integrates hedonic enjoyment and price-saving orientation as predictive factors, alongside the level of COVID-19 awareness as a moderating variable. An online survey was administered, and primary data was collected by distributing an electronic questionnaire link randomly via email and social media platforms. Employing a sampling judgement technique, 260 millennials in Indonesia who utilize the SE (Gojek) mobile app were identified as participants. Results from the PLS-SEM analysis reveal that performance expectancy, effort expectancy, social influence, price-saving orientation, and habits exert a favorable and significant impact on behavioral intentions. Furthermore, habits and behavioral intentions were found to significantly influence the actual usage of the SE app among millennials. Conversely, hedonic enjoyment demonstrated no significant influence on behavioral intentions. Moreover, the moderating role of COVID-19 awareness was observed to both enhance and diminish direct relationships. The implications, both theoretical and practical, along with recommendations for future research, are deliberated upon.